Following Germany's Lead : Using International Monetary Linkages to Identify the Effect of Monetary Policy on the Economy. (IMF Working Papers; Working Paper, 2005)
Forward-looking behavior on the part of the monetary authority leads least squares estimates to understate the true growth consequences of monetary policy interventions. We present instrumental variables estimates of the impact of interest rates on real output growth for several European countries, using German interest rates as the instrument. We show that the difference between least squares and instrumental variables estimates provides bounds for the degree of endogeneity in monetary policy. The results confirm a considerable downward bias of estimates that do not account for potential forward-looking monetary policy decisions. The bias is higher for countries whose monetary policy was more independent of Germany.